Daratumumab-Based Quadruplet Versus Triplet Induction Regimens in Frontline Transplant-Eligible Newly Diagnosed Multiple Myeloma: A Systematic Review and Meta-Analysis - Souto Filho, Joao Tadeu Damian; Cantadori, Lucas Oliveira; De Queiroz Crusoe, Edvan; Hungria, Vania; Maiolino, Angelo (American Society of Hematology, 2024)
Introduction: The treatment landscape for transplant-eligible newly diagnosed multiple myeloma (TE-NDMM) patients is evolving rapidly. Triplet regimens have traditionally been standard induction therapy until the emergence of daratumumab-based quadruplet regimens. Adding daratumumab to triplets has shown feasibility and improved outcomes in terms of response rates and progression-free survival (PFS). However, the impact on long-term outcomes, particularly overall survival (OS), remains uncertain. Methods: We conducted a systematic review (SR) and meta-analysis (MA) to compare survival outcomes associated with the addition of daratumumab to backbone induction regimens in patients with TE-NDMM. This review adhered to Cochrane Collaboration and PRISMA guidelines and was registered on PROSPERO. The search strategy was developed using pre-specified PICOTS criteria. Included studies met the following eligibility criteria: 1) randomized clinical trials and observational controlled studies; 2) that compared daratumumab-based quadruplet induction regimens to triplet induction regimens; 3) in TE-NDMM patients; 4) reported the outcomes of interest: OS and PFS; and 5) with a minimum follow-up of 18 months. We systematically searched PubMed, Embase, and Cochrane Library databases from January 2019 to June 2024, and the gray literature through manual searches of references, trial registries, and major hematology meeting abstracts. Data extraction and quality assessment were conducted independently by two authors using predefined criteria. Pooled hazard ratios (HR) and 95% confidence intervals (CI) were calculated using a DerSimonian and Laird random-effects model. Statistical analyses, along with forest plots and pooled survival curves, were conducted using Review Manager (version 5.4.1) and R (version 4.4.1). Results: Four studies involving 3,327 TE-NDMM patients were included, comprising three randomized controlled trials (CASSIOPEIA, GRIFFIN, and PERSEUS) and one non-randomized controlled study (Joseph et al., 2023). Daratumumab-based quadruplet regimens were administered to 1,328 (40%) patients. The weighted median follow-up duration was 51.7 months, with a range from 19.1 to 88.4 months. Across three studies, daratumumab in combination with bortezomib, lenalidomide, and dexamethasone (D-VRD) was compared to VRD, while one study compared daratumumab with bortezomib, thalidomide, and dexamethasone (D-VTD) to VTD. The weighted median patient age was 60 years, 57% were male, 45.6% had ISS stage I, 36.4% had ISS stage II, 17.9% had ISS stage III disease, and 17.5% of patients had a high-risk cytogenetic profile. The addition of daratumumab to first-line backbone regimens significantly improved OS (pooled HR 0.60; 95% CI 0.48-0.75; p < 0.00001; I2 = 0%) and PFS (pooled HR 0.49; 95% CI 0.37-0.65; p < 0.00001; I2 = 52%). Per-protocol subgroup analysis comparing D-VRD and VRD demonstrated that the daratumumab-based regimen significantly extended both OS (pooled HR 0.68; 95% CI 0.48-0.97; p = 0.03; I² = 0%) and PFS (pooled HR 0.41; 95% CI 0.31-0.54; p < 0.00001; I² = 0%). Conclusions: This meta-analysis consolidates evidence that daratumumab-based quadruplet regimens in frontline treatment of TE-NDMM significantly improve overall survival compared to triplet regimens. These findings could guide the selection of optimal first-line treatments in the absence of long-term follow-up data from ongoing randomized trials.